The “Third-Victimization”: The Cybervictimization of Sexual Assault Survivors and Their Families - Clevenger, Shelly (Journal of contemporary criminal justice, 2021)
Sexual assault has a devastating effect on survivors as well as their family and friends (i.e., secondary survivors). Research shows that survivors’ abilities to cope in the aftermath of sexual trauma are particularly difficult in the “internet” age. This struggle stems from the abilities of perpetrators to use cyberspace to abuse, harass, and threaten survivors vis-à-vis various cybercrimes: cyberstalking, cybersexual abuse, and cyberfraud. Indeed, a survivor in this study referred to the cybervictimizations as the “third-victimization” because it followed the sexual assault (first) and the “revictimization” experienced during the pursuit of justice (second). This article presents the results of semistructured interviews about the third-victimization of 48 female survivors and 89 secondary survivors, the family of the survivor. These results show that all primary and most secondary survivors (91%) experienced at least one third-victimization, with a majority experiencing multiple forms.